1996
DOI: 10.1002/eji.1830260230
|View full text |Cite
|
Sign up to set email alerts
|

Binding of nucleosomes to a cell surface receptor: Redistribution and endocytosis in the presence of lupus antibodies

Abstract: In the present study, we sought evidence for a surface nucleosome receptor in the fibroblastic cell line CV-1, and questioned whether anti-double-stranded (ds) DNA and/or anti-histone autoantibodies could recognize and influence the fate of cell surface-bound nucleosomes. 125I-labeled mononucleosomes were shown to bind to the cell layer in a specific, concentration-dependent and a saturable manner. Scatchard analysis revealed the presence of two binding sites: a high-affinity site with a Kd of approximately 7n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 70 publications
1
66
1
5
Order By: Relevance
“…Histone gel analysis (28,29) of the mononucleosome preparations demonstrated the presence of the core made up of the 4 histones in equimolar amounts, indicating that this preparation yielded "intact" mononucleosomes (26).…”
Section: Patientsmentioning
confidence: 97%
“…Histone gel analysis (28,29) of the mononucleosome preparations demonstrated the presence of the core made up of the 4 histones in equimolar amounts, indicating that this preparation yielded "intact" mononucleosomes (26).…”
Section: Patientsmentioning
confidence: 97%
“…Both in vivo transfer experiments with nucleosomes complexed with lupus antibody [23,24] and GBM binding in vitro of sera from lupus-prone mice and SLE patients [25,26] have indicated that nucleosomes, either within circulat-ing immune complexes or present in situ on target tissues, mediate binding of lupus autoantibodies to glomerular antigens. Furthermore, there is also evidence that the nucleosome could exert direct effects on cell function, presumably through binding to specific surface receptors [27][28][29]. Polyclonal B cell activation by nucleosomes has been demonstrated both with murine and human lymphocytes [30,31] and interleukin-6 (IL-6) secretion has been observed after interaction of nucleosomes with murine spleen cells [32].…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies (including the representative monoclonal 2C5 antibody, mAb 2C5) demonstrate nucleosome-restricted specificity and recognize various live cancer cells via the cancer cell surfacebound nucleosomes released from apoptotically dying cancer cells (18). This phenomenon stems from the fact that live cancer cells from various tumors and cell lines seem to carry specific binding sites for nucleosomes on their surface (19). Previous studies have clearly demonstrated that, in addition to their own anticancer activity (20), such antibodies can serve as tumor-targeting ligands.…”
mentioning
confidence: 99%